Pengaruh Bantuan Langsung Tunai Dana Desa (BLT DD) Terhadap Kesejahteraan Masyarakat Desa Parenring, Kecamatan Lilirilau, Kabupaten Soppeng - Maspawati Maspawati; Bakri Bakri; Afdal Afdal (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This study aims to determine how big the Influence of Direct Village Fund Cash Assistance (BLT DD) on the Welfare of the People of Parenring Village, Lilirilau District, Soppeng Regency, using survey research, namely only a portion of the population is used as a sample. The population in this study were 71 people, then to determine the sample used the Yamane taro formula and produced a sample of 42 people, the sample used was random sampling (random sample). Data collection techniques using observation, questionnaires and documentation. For data analysis techniques used are quantitative descriptive analysis techniques and quantitative associative analysis techniques. The results showed that there was a fairly strong influence between BLT DD on community welfare in Parenring Village, Lilirilau District, Soppeng Regency with a correlation value (R) of 0.511. This shows that the percentage contribution of the BLT DD variable to community welfare is 26.1%, while the remainder is 100% - 26.1% = 73.9% which is influenced or explained by other variables.